Valorization of Aquaculture Byproducts through Enzymatic Hydrolysis: Production of Peptides with Antioxidant and ACE-Inhibitory Activity - Ambrosi, Vanina; Martinez, Fernanda Gabriela; Vasquez Mazo, Priscilla; Guidi, Silvina Mabel; Diaz, Gabriela Esther; Szerman, Natalia (INTA y Sbera, 2025)
Poster